2015
DOI: 10.1589/jpts.27.239
|View full text |Cite
|
Sign up to set email alerts
|

The effects of mouth opening on changes in the thickness of deep cervical flexors in normal adults

Abstract: [Purpose] The purpose of this study was to identify changes in the thickness of the deep cervical flexors (DCFs) according to the degree of mouth opening (MO) in normal adults. [Subjects] The study’s subjects were 50 normal adults (30 men, 20 women). [Methods] Ultrasound was used to obtain images of muscles, and the NIH ImageJ software was used to measure the thickness of each muscle. [Results] An increase in MO resulted in a corresponding increase in the thickness of the DCFs, and in isometric exercises (IEs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Alterations in body posture such as abnormal cervical spine position (for example lack of cervical lordosis) lead to hyperactivity of deep cervical flexors which are related to not only deformities in neck but also in shoulder girdle, head (protraction of head), kyphosis [20][21][22]. We found that the deviation of head position affected almost all children and in the setting of shoulder girdle over it affected 70% of children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations in body posture such as abnormal cervical spine position (for example lack of cervical lordosis) lead to hyperactivity of deep cervical flexors which are related to not only deformities in neck but also in shoulder girdle, head (protraction of head), kyphosis [20][21][22]. We found that the deviation of head position affected almost all children and in the setting of shoulder girdle over it affected 70% of children.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the deviation of head position affected almost all children and in the setting of shoulder girdle over it affected 70% of children. It should be noted that in the future such a posture as the forward-head and roundedshoulder posture may play a role in the development of shoulder pain and pathologic conditions [21,22]. For this reason, improving children's body posture should be a prophylactic aim of school teachers [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…The neck pain group that had been treated by both the ROM technique (joint mobilization) and the physical therapy technique, displayed better results, thereby demonstrating that flexion, extension, left lateral bending, right lateral bending, left rotation, and right rotation were all improved in comparison to the other neck pain group, which had only been treated using the physical therapy technique 19 ) . A study, in which the head-neck flexion exercise was performed using sling equipment, reported that the ROM for flexion and extension was significantly improved 20 ) .…”
Section: Discussionmentioning
confidence: 99%